2020
DOI: 10.1186/s12891-020-03805-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative DCE-MRI: an efficient diagnostic technique for evaluating early micro-environment permeability changes in ankylosing spondylitis

Abstract: Background In the management of early inflammatory joint of ankylosing spondylitis (AS), there is a need for reliable noninvasive quantitative monitoring biomarker to closely assess status of synovitis progression. Cognizant to this,studies geared on improving techniques for quantitative evaluation of micro-environment permeability of the joint space are necessary. Such improved techniques may provide tissue perfusion as important biological parameters and can further help in understanding the origin of early … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In our study, we evaluated the changes of DCE-MRI parameters and ESR, CRP, and DAS-28 of patients with RA before and after therapy and found notable decreases of SSmax, REE, ESR, CRP, and DAS-28 in patients after therapy. Through correlation analysis, we also found that SSmax and REE were positively correlated with ESR, CRP, and DAS-28, which indicated that SSmax and REE might become the observation indexes of rheumatoid arthritis development [ 23 ]. DCE-MRI parameters were calculated according to ROI time-signal intensity curves.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we evaluated the changes of DCE-MRI parameters and ESR, CRP, and DAS-28 of patients with RA before and after therapy and found notable decreases of SSmax, REE, ESR, CRP, and DAS-28 in patients after therapy. Through correlation analysis, we also found that SSmax and REE were positively correlated with ESR, CRP, and DAS-28, which indicated that SSmax and REE might become the observation indexes of rheumatoid arthritis development [ 23 ]. DCE-MRI parameters were calculated according to ROI time-signal intensity curves.…”
Section: Discussionmentioning
confidence: 99%